Cardiac arrest in the delivery room - Guerrero, Carlos (2015)
In this symposium has been accepted that heart failure is the result of multiple pathological conditions related on one side to itself heart and its ability to contract and on the other hand, disturbances of peripheral circulation, either the circuit initiated in the left ventricle or more frequently the pulmonary circuit.